Penerapan UU No. 18 Tahun 2008 Terhadap Etika Masyarakat Lingkungan V Kelurahan Sidorejo Dalam Membuang Sampah - Tawarika M. Pandiangan; Alissa P. Simbolon; Mantasia Hasibuan; Mario Fany Manurung; Rahmi Siregar; Florensia Silaban; Ramsul Nababan; Maulana Ibrahim (Universitas 17 Agustus 1945 Semarang, 2024)
Littering has become a problem for environmental hygiene and health threatening people in the red zone. It is feared that it becomes a seductive ethic. The ward head serves as a local government geographically a territory closer to the community being led. As a result of his hand being extended to assist his duty, which includes the administration of environmental order and security surveillance and the dynamics of community life has been observed and faced by the ward's head. The study was aimed at getting information from a facto face perspective on the ethics of the environment community concurred with government policy on keeping the environment clean, including the disposal of trash in its place. This method of research uses qualitative research using data collection techniques through semi structured interviews. The results showed that there was no crucial problem with the people's ethic of removing garbage and local governments had undertaken socialization to maintain community hygiene and that garbage disposal workers had been radiating governments to help transport the garbage on a regular basis. The community's ethical cooperation and the attention of the government have succeeded in turning the neighborhood into a green zone on environmental hygiene.